E-WOM Orientation Strategy as a Catalytic Dimension in Enhancing Brand Equity of Craftonesia - Havif Wahyu Saputra; Irsal Fauzi (Return : Study of Management, Economic and Bussines, 2025)
This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), digital marketing strategy, and innovation on the brand equity of Craftonesia, an MSME in Semarang that produces woven crafts from waste paper. The research method used is qualitative with a case study approach, which involves in-depth interviews and observation. The results showed that E-WOM plays a significant role in increasing brand awareness and consumer purchase intention. In addition, a digital marketing strategy that includes Search Engine Optimization (SEO) and Search Engine Marketing (SEM) helps Craftonesia reach a wider audience. The research also identified challenges facing Craftonesia, including limited human resources and digital marketing. The conclusion of this study is that a combination of E-WOM, consistent branding, and effective digital marketing strategies are key to Craftonesia's success in increasing brand equity. The implications of this study recommend Craftonesia to partner with micro-influencers and increase customer engagement through UserGenerated Content (UGC) and collaboration with local communities.